1988
DOI: 10.1029/gl015i006p00601
|View full text |Cite
|
Sign up to set email alerts
|

Displacements and tilts from dip‐slip faults and magma chambers beneath irregular surface topography

Abstract: Surface displacements and tilts due to buried deformation sources are influenced by topography. The leading‐order corrections due to topography of arbitrary profile, but small slope, are determined for dip‐slip faults (edge dislocations) and magma bodies (lines of inflation) in a two‐dimensional elastic medium. The vertical displacement correction is simply the product of the topography and the horizontal normal strain due to the source in a flat half‐space. The correction for a normal fault beneath an idealiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 9 publications
(3 reference statements)
1
48
0
Order By: Relevance
“…Several studies on the topographic effect ͑McTigue and Stein, 1984;McTigue and Segall, 1988;Cayol and Cornet, 1998;Williams and Wadge, 1998;Folch et al, 2000;Charco et al, 2002;Trasatti et al, 2003;Lungarini et al, 2005͒ support the conclusions that topography has a significant effect on the deformation field and that in many cases the flat half-space approximation could lead to erroneous interpretation of observed ground deformation.…”
Section: The Effect Of Topographymentioning
confidence: 82%
“…Several studies on the topographic effect ͑McTigue and Stein, 1984;McTigue and Segall, 1988;Cayol and Cornet, 1998;Williams and Wadge, 1998;Folch et al, 2000;Charco et al, 2002;Trasatti et al, 2003;Lungarini et al, 2005͒ support the conclusions that topography has a significant effect on the deformation field and that in many cases the flat half-space approximation could lead to erroneous interpretation of observed ground deformation.…”
Section: The Effect Of Topographymentioning
confidence: 82%
“…While such models have been quite successful at fitting surface measurements, it is clear that local topographic relief can introduce misinterpretation into source parameter estimation. MCTIGUE and STEIN (1984) and MCTIGUE and SEGALL (1988) studied the effect of topography by means of a two-dimensional model. CAYOL and CORNET (1998) and WADGE (1998, 2000) calculated the effect of the volcanic relief caused by a dilatational source in a purely elastic medium.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, McTigue and Segall [1988], investigated the effects of topography on surface displacements by using a plane-symmetric approximation. Cayol and Cornet [1998] considered an axial symmetrical volcano with average slopes of flanks ranging from 0° to 30° and they showed that the flattening of the deflation in the summit area is probably a topographic effect: the steeper the volcano, the lower the central uplift.…”
Section: Accepted Manuscriptmentioning
confidence: 99%